Penerapan Metode MAUT Dalam Pemilihan Pegawai Terbaik Pada Kantor Pertanahan Kota Medan - Josua Leonardo Hamonangan Lumban Tobing; Niko Fransisko Aritonang (TIN: Terapan Informatika Nusantara, 2022)
The Medan City National Land Agency is a government agency engaged in the land sector in accordance with the ATR/BPN ministry regulations which is responsible for all problems in the land sector. The Medan City National Land Agency is coordinated by the regional office and technically the administration is under the head of the Medan North Sumatra provincial land office. At the Medan City National Land Agency office, it is necessary to select the best employees in order to increase employee morale in carrying out services. In selecting the best employee the author uses the Multi Attribute Utility Theory (MAUT) method, this method is a method used to solve situations where several choices have different properties and interact with each other. From the results of the discussion that has been carried out by applying the MAUT method in accordance with the alternatives according to the criteria applied to the Medan City National Land Agency office, the ranking results obtained at the first level A4 are 0.88714 on behalf of Melda Sari Bancin. It is hoped that this research can help provide more precise information with more accurate calculations to be able to make decisions and be a solution in solving problems